The Influence of Financial Education and Financial Literacy in Improving Financial Management Behavior in Tasikmalaya MSMEs Business Actors - Rosliyati, Ati; Iskandar, Yusuf (International Journal on Social Science, Economics and Art, 2024)
Financial education plays a crucial role in the sustainability and development of micro, small, and medium enterprises (MSMEs). This study aims to examine the influence of financial education and financial literacy on financial management behavior. The research uses a quantitative approach with a survey method. A quantitative approach was chosen to observe the effect of financial education and literacy on the financial management behavior of MSMEs in Tasikmalaya City. The research instruments consist of questionnaires related to financial education, the level of financial literacy (adapted from the Financial Literacy Index by OJK) assessing basic financial knowledge, and questionnaires related to financial management behavior. The data analysis technique uses regression tests to determine the influence of the independent variables on the dependent variable. The conclusion of this study indicates that financial education and financial literacy significantly impact financial management behavior. This underscores the importance of these two factors in improving financial management behavior among MSME players.